(untitled) - Dreyer, Willem Akkerhuys (Wim)

A critique of land reform in Zimbabwe from the perspective of Miroslav Volf's public theology (University of Pretoria, 2025)
Thesis (PhD (Church History and Church Polity)--University of Pretoria, 2024.